2021
DOI: 10.1108/ijlm-01-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in agribusiness: an exploratory investigation from a supply chain perspective during the COVID-19 crisis

Abstract: PurposeThe COVID-19 pandemic has badly affected the global economy. The use of social capital as a resource to diversify agribusiness to get more customers and improve the agricultural supply chain is a considerable issue to explore. This study aims to develop a comprehensive measurement of social capital and examine its effect on the intention to diversify agribusiness. From a supply chain perspective, it uses theory of planned behavior (TPB) and resource-based view (RBV).Design/methodology/approachThe study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 151 publications
(286 reference statements)
12
54
0
1
Order By: Relevance
“…Finally, the study also showed that the interaction between CSC and RSC is significant and positive. This result provides empirical evidence for the implication of Lang et al (2021b) regarding the interplay between aspects of social capital in the agribusiness context in an emerging market. The finding also supports and increases the generalizability of the previous works of some scholars in this area (e.g.…”
Section: Results Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Finally, the study also showed that the interaction between CSC and RSC is significant and positive. This result provides empirical evidence for the implication of Lang et al (2021b) regarding the interplay between aspects of social capital in the agribusiness context in an emerging market. The finding also supports and increases the generalizability of the previous works of some scholars in this area (e.g.…”
Section: Results Discussionmentioning
confidence: 65%
“…Therefore, this research aims to investigate the influence of these two social capital types (i.e. CSC and RSC) on agricultural entrepreneurs' SAE intentions in the context of the negative impacts of COVID-19 (Singh et al, 2020;Sodhi et al, 2021), global issues (Enders and Remig, 2016;Sazvar et al, 2018) and the needs for sustainable agribusiness development (Squalli and Adamkiewicz, 2018;Kumar et al, 2021;Lang et al, 2021b).…”
Section: Social Capital Theory and The Extended Theory Of Planned Beh...mentioning
confidence: 99%
See 2 more Smart Citations
“…For redesigning work, it is advisable to incorporate work elements that have been extended through our analysis (section 5) and theoretical contribution (section 6). The application should consider how the HRD managers or other managers find themselves in manufacturing alone or clubbed with service orientation (Lang et al, 2021a(Lang et al, , 2021b. Further, collaborative HRD practices (Chen et al, 2021) must cater to work roles that are becoming complex (Lee and Lee, 2018).…”
Section: Practical Implicationsmentioning
confidence: 99%